Relation of Novel Echocardiographic Measures to Invasive Hemodynamic Assessment in Scleroderma‐Associated Pulmonary Arterial Hypertension1. Issue 9 (September 2014) - Gopal, Deepa M.; Doldt, Bryan; Finch, Kim; Simms, Robert W.; Farber, Harrison W.; Gokce, Noyan
<x xml:space="preserve">Abstract</x> Objective Systemic sclerosis (SSC; scleroderma)–associated pulmonary arterial hypertension (PAH) is a major cause of mortality in SSc patients and represents an important diagnostic and therapeutic target. Our aims were to evaluate the relationship between echocardiogram‐derived right‐sided heart hemodynamics and gold standard right‐sided heart catheterization (RHC) measurements in a scleroderma population and to investigate whether this relationship is modified by a subset of pulmonary hypertension. Methods We performed RHC and echocardiography on the same day, with pulmonary function testing in 21 consecutive subjects with scleroderma and precapillary pulmonary hypertension (mean ± SD age 57 ± 10 years, 81% women). Results RHC measures, including pulmonary arterial systolic and mean pressure and pulmonary vascular resistance (PVR), correlated strongly with echocardiogram‐derived data. RHC‐derived PVR was negatively associated with right ventricular (RV) systolic performance, as measured by tricuspid annular plane systolic excursion (TAPSE; rho = −0.70, P < 0.001), tissue Doppler tricuspid s′ velocity (rho = −0.68, P = 0.002), and RV fractional area change (rho = −0.78, P < 0.001). Correlations with TAPSE and s′ velocity were strengthened when forced vital capacity %/diffusing capacity of the lung for carbon monoxide % ≥1.6 was used to identify pure PAH phenotypes in SSc. Bland‐Altman analyses demonstrated strong agreement between RHC and echocardiogram‐derived hemodynamic measures. Conclusion Our findings suggest that echocardiography may play a clinical role in identifying pulmonary hypertension and RV dysfunction noninvasively, particularly in a subset of SSc patients stratified by pulmonary function testing. This method may establish specific disease phenotypes with differential cardiovascular impact and prove useful as a marker of disease progression/risk stratification in SSC patients that warrants further investigation in larger cohorts.